Islam di India pada Masa Kepemimpinan Sultan Akbar (1556-1605 M) - Rizqina Tsania; Helmi Mukaromah; Rifatul Muazaroh (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The spread of Islam in India is inseparable from the influence of Mughal power. One of the sultans who had a big role in this matter was Sultan Jalaluddin Akbar or better known as Sultan Akbar. He was the third sultan who came to power in 1556-1605 AD. In this article, we will discuss the biography of Sultan Jalaluddin Akbar, the achievements of Sultan Akbar during his reign in India, and the development of Islam in India at that time. The research method used in this article is the historical research method. The results of this study indicate that during the reign of Sultan Akbar, the Moghul empire managed to dominate India widely to Gujarat. Sultan Akbar also made a policy in the form of acculturation between Islamic culture and local Indian culture which eventually gave birth to an Indian-Islamic culture. This acculturation is an attempt to quell Indian society's rejection of Islam.